2018
DOI: 10.48550/arxiv.1802.10550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exclusive double quarkonium production and generalized TMDs of gluons

Abstract: Being the "mother distributions" of all types of two-parton correlation functions, generalized transverse momentum dependent parton distributions (GTMDs) have attracted a lot of attention over the last years. We argue that exclusive double production of pseudoscalar quarkonia (ηc or η b ) in nucleon-nucleon collisions gives access to GTMDs of gluons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
(86 reference statements)
0
18
0
Order By: Relevance
“…The observable is dominated by the gluonic contributions if the dijet is a pair of heavy quark and antiquark [390], or at small-x [391], which can be very robust at EIC with high energy. Meanwhile, it is also suggested that F q 14 can be measured through the same asymmetry in the exclusive double Drell-Yan process πN → (l − 1 l + 1 )(l − 2 l + 2 )N [392], as well as the exclusive double production of pseudoscalar quarkonia (η c or η b ) in nucleon-nucleon scattering [393]. Again, the analyses in [390,393] are only at tree level, while complication of rapidity renormalization has not been considered.…”
Section: Parton Orbital Angular Momentummentioning
confidence: 99%
“…The observable is dominated by the gluonic contributions if the dijet is a pair of heavy quark and antiquark [390], or at small-x [391], which can be very robust at EIC with high energy. Meanwhile, it is also suggested that F q 14 can be measured through the same asymmetry in the exclusive double Drell-Yan process πN → (l − 1 l + 1 )(l − 2 l + 2 )N [392], as well as the exclusive double production of pseudoscalar quarkonia (η c or η b ) in nucleon-nucleon scattering [393]. Again, the analyses in [390,393] are only at tree level, while complication of rapidity renormalization has not been considered.…”
Section: Parton Orbital Angular Momentummentioning
confidence: 99%
“…Related work includes [96], where it was suggested to study forward diffractive quarkonia production in p + p collisions to probe the Weizsäcker-Williams gluon distribution and [97], where access to the gluon Wigner distributions via ultraperipheral p + A collisions was discussed. Exclusive double production of pseudoscalar quarkonia and its relation to the gluon Wigner distributions in nucleon-nucleon collisions was explored in [98]. Exclusive diffractive two-and three-jet production in photon-hadron scattering within k T factorization and the cancellation of IR, collinear and rapidity singularities for the two-jet cross section was studied in [99].…”
Section: Introductionmentioning
confidence: 99%
“…In [434] it was shown that the production of two pseudoscalar quarkonia (e.g. η c η c , η c η b or η b η b ) in exclusive hadronic collisions, where both hadrons remain intact, is a direct probe of GTMDs for gluons at moderate x (Fig.…”
Section: Accessing Wigner Functions Through Q-pair Productionmentioning
confidence: 99%